Dimensions of Divine Love Perspective of Rabi'ah Al-’Adawiyyah and Jalal Al-Din Al-Rumi - Nana Suciana; Encung, Encung (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research discusses the dimensions of divine love according to Rabi’ah Al-’Adawiyyah and Jalal Al-Din Al-Rumi. The main focus of this research is to understand and compare the dimensions of divine love according to the two figures, which is seen as the highest expression of the human relationship with God. The research method used is qualitative, with the type of library research (literature study), descriptive, interpretative, and comparative analysis. The results showed that according to Rabi’ah Al-’Adawiyyah love is pure without reciprocation and sincere love without being accompanied by reasons, for him love is the perfect form of devotion. Whereas according to Jalal Al-Din Al-Rumi he argues that the first thing God created was love because it is with the assistance of love that everything on this earth can run and move with good harmony. The similarity of the dimensions of divine love according to both of them is that they agree that love is the core of human relations with God. And the difference for Rabi'ah Al-'Adawiyyah, love is the highest form of total submission, while for Jalal Al-Din Al-Rumi, love is a universal force that encourages all creation to unite with God.